ANALYSIS OF SOIL FERTILITY STATUS ON AGRICULTURAL LAND IN WEST SINJAI DISTRICT - Ahmad Hidayat; Ahmad Fauzan Adzima; Noor Husna Khairisa (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2022)
Soil fertility status not only depicts types of nutrients but also the available nutrients content in the soil. Soil fertility status that is used in agriculture has wide variations and influenced by soil management. Soil management determines of plant growth and its productivity. Three from nine districts in Sinjai Regency are designated as agropolitan areas, one of which is West Sinjai District. This district is considered to be very potential for development of agricultural sector because geographically it is located on high latitude area. The productivity of agricultural land is largely determined by the existing soil quality, which is reflected in its fertility status. Therefore, the existing soil needs to be evaluated for its fertility status, thus the input can be in accordance with the needs of the soil. The method used in this research are survey method, laboratory analysis, and descriptive analysis. The results showed that the soil fertility status at each location is in low. This is influenced by the parameter values of the KTK parameters, KB, P2O5, K2O, and C-organic.